2015
DOI: 10.1186/s12876-015-0414-z
|View full text |Cite|
|
Sign up to set email alerts
|

Liver and spleen transient elastography predicts portal hypertension in patients with chronic liver disease: a prospective cohort study

Abstract: BackgroundTo assess correlation between liver or spleen stiffness measurement by transient elastography (TE) and hepatic venous pressure gradient (HVPG) in patients with chronic liver disease as well find optimal and rule in/rule out cut-offs for prognosis of clinically significant (CSPH) and severe (SPH) portal hypertension.MethodsIn this prospective study patients with different chronic liver diseases were included. TE was performed at the same day prior to HVPG measurement. HVPG was measured using catheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…Our study hence showed that S‐SWE is a possible tool to assess CSPH, similar to TE . On the basis of these significant results, we set for the first time the cut‐off values for S‐SWE to predict accurately portosystemic pressure gradients of 5, 10 and 12 mm Hg.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our study hence showed that S‐SWE is a possible tool to assess CSPH, similar to TE . On the basis of these significant results, we set for the first time the cut‐off values for S‐SWE to predict accurately portosystemic pressure gradients of 5, 10 and 12 mm Hg.…”
Section: Discussionmentioning
confidence: 72%
“…Transient elastography (TE) has already been considered not only a good tool for the evaluation of liver fibrosis, but also for the diagnosis of portal hypertension. [21][22][23][24][25] Therefore, TE measurements have found their way into the guidelines for diagnosing, stratifying and classifying liver diseases. 25 Also in the last Baveno meeting, TE of the liver has been recommended to stratify patients at risk for varices.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen stiffness (SS) measured by tissue elastometry has been showed to be significantly correlated to the hepatic venous pressure gradient . Moreover, the capacity of SS was measured either by tissue elastometry or by ARFI in identifying patients with portal hypertension (i.e., hepatic venous pressure gradient [HVPG] > 10 mmHg); clinically significant portal hypertension (HVPG > 12 mmHg) or varices at endoscopy has been shown to be superior to liver stiffness (LS) although not in all studies . Thus, SS can be considered a promising method for the non‐invasive diagnosis of portal hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the capacity of SS was measured either by tissue elastometry [10][11][12] or by ARFI 13 in identifying patients with portal hypertension (i.e., hepatic venous pressure gradient [HVPG] > 10 mmHg); clinically significant portal hypertension (HVPG > 12 mmHg) or varices at endoscopy has been shown to be superior to liver stiffness (LS) although not in all studies. [14][15][16] Thus, SS can be considered a promising method for the non-invasive diagnosis of portal hypertension. [17][18][19] However, little is known on the relationship between the modification of the portal pressure and the modification of splenic stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that SS assessed by elastography was a more effective parameter with high diagnostic accuracy for identifying and grading EV than LS [14,15]. Conversely, other studies have concluded that spleen elastography is not superior to liver elastography in predicting EV for its inconstant accuracy, poor repeatability and highly unreliable measurement [1618]. In 2014, a meta-analysis summarized the accuracy of SS measurement in predicting EV.…”
Section: Introductionmentioning
confidence: 99%